Study of the protective effect of alcoholic extract of Silybum (Gundelia tournefortii) plant leaves on nonalcoholic fatty liver disease induced by carbon tetrachloride in white mice and its comparison with atorvastatin - Assaad, Youssef Anour; Dreous, Mohamed; Salameh, Reem (Journal of agricultural, environmental and veterinary sciences, 2021)
The study aimed to test the protective effect of the alcoholic extract of Gundelia tournefortii leaf on non-alcoholic fatty liver disease induced in white mice and to identify some of the biochemical and histological changes associated with that.The study was conducted on forty male Mice, and it was divided equally into four groups, Mice of the first experimental group (control) were injected with NaCl physiological solution (0.9%) for 10 weeks, Mice of the second group were injected (i.p) with a single dose of ccl4 (1 ml/ kg) to induce greasiness, and left (24) hours before work, Mice of the third group were injected only once with a dose of ccl4 (1 ml/ kg) and daily doses of the alcoholic extract of the leaves of the Gundelia tournefortii plant for 10 weeks (250 mg/ kg of body weight), Group IV mice were injected intraperitoneally only once with a dose of ccl4 (1 ml/ kg) and with daily doses of atorvastatin (250 mg/ kg body weight) for 10 weeks.The results of the histological study of the livers of mice of the second experimental group showed the emergence of clear lubrication, which some cases reached the point of necrosis (localization of the nucleus in the periphery), while the results of the livers of mice of the third and fourth groups showed a clear improvement in the hepatic cell compared with the second group, where fat was minimal (Natural kernel with no inflammatory foci) and this confirms the important protective role of Gundelia tournefortii extract with its active ingredients (besides atorvastatin) against the nonalcoholic lipidosis.
Keywords: Mice; nonalcoholic fatty liver; Gundelia tournefortii